Evaluation of the impact of milk quota - case study Germany - Werner Kleinhanß; Frank Offermann; Markus Ehrmann (Johann Heinrich von Thünen-Institut (vTI), 2010)
At the time of the introduction of the quota system the structure of dairy production in Germany was rather unfavourable. Since 1993, German policy generally aimed at improving quota mobility. The introduction of transfers without land in 1993 facilitated farm growth and the transfer of resources and production to the better farm managers and to locations best suited for dairy production; however the latter was restricted by the regional limitations of the trading zones. The quota auctions introduced in 2000 significantly improved the transparency of quota markets. Larger regional shifts in production will be enabled by the recent reduction of the number of trading zones. Overall, structural change in dairy production has been strong (halving the number of dairy farms every ten years) despite the limitations by the quota system. Still many regions in Germany, notably the case study region of Bavaria, are characterised by small farm structure, where the main share of milk production is still realised by small and medium sized farms. – – Zur Zeit der Einführung des Quotensystems war die Struktur der Milchproduktion in Deutschland eher ungünstig. Durch die anfängliche strikte Flächenbindung der Quote wurden strukturelle Anpassungen behindert. Die Einführung des Quotentransfers ohne Land im Jahr 1993 erleichterte betriebliches Wachstum und die Verlagerung der Quote zu den besten Wirten und Standorten (innerhalb der Übertragungsgebiete). Mit der 2000 eingeführten Übertragung über Börsen wurde die Flächbindung aufgehoben und eine bessere Transparenz auf dem Quotenmarkt erreicht. Größere regionale Verlagerungen der Milcherzeugung ergeben sich seit Verringerung der Anzahl der Handelszonen seit 2007. Trotz der Beschränkungen durch das Quotensystem ist der Strukturwandel stark ausgeprägt mit einer annähernden Halbierung der Zahl der Milcherzeuger im Zehnjahreszeitraum.
urn:nbn:de:gbv:253-201010-dn047019-2
Keywords: Q12; Q18; Q51; 330; Milk quota; Agricultural policy; structural change; environmental impacts; Milchquote; Agrarpolitik; Strukturwandel; Umwelteffekte; EU-Milchmarktordnung; Wirkungsanalyse; Milchviehhaltung; Agrarstruktur; Strukturwandel; Deutschland